1980
DOI: 10.1080/0361697800040306
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and Job Satisfaction Characteristics of Florida Community College Faculty

Abstract: The demographic and job satisfaction characteristics of Florida community college faculty were studied in Florida's 28 community colleges. A total of 1,116 faculty responded in the fall of 1977 to an instrument developed to measure faculty characteristics and attitudes. The results showed that the Florida faculty is a satisfied faculty with over 95% reporting that they were satisfied with community college work as a career and with 72% stating that they plan to stay in the community college field until they re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Studies conducted specifically with community college faculty consistently report moderate to high levels of satisfaction (Benoit & Smith, 1980;Hutton & Jobe, 1985;Finley, 1990;Diener, 1985) for both full and part-time faculty (Benoit & Smith, 1980;Antony & Valadez, 1998;Bowman, 1995;Flowers, 2005). Only one study (Hill, 1983) indicates lower levels of satisfaction.…”
Section: Higher Education Faculty Job Satisfactionmentioning
confidence: 95%
See 1 more Smart Citation
“…Studies conducted specifically with community college faculty consistently report moderate to high levels of satisfaction (Benoit & Smith, 1980;Hutton & Jobe, 1985;Finley, 1990;Diener, 1985) for both full and part-time faculty (Benoit & Smith, 1980;Antony & Valadez, 1998;Bowman, 1995;Flowers, 2005). Only one study (Hill, 1983) indicates lower levels of satisfaction.…”
Section: Higher Education Faculty Job Satisfactionmentioning
confidence: 95%
“…Faculty report increased satisfaction (Ormsby & Ormsby, 1988;Benoit & Smith, 1980;Hill, 1982;Finley, 1990), decreased satisfaction (Borjas, 1979;Ladd & Lipset, 1973), or no significant difference in satisfaction (Ormsby & Watts, 1991). In an attempt to account for these unclear findings, scholars (Herzberg, Mausner, & Snyderman, 1959;Maslow, 1954;Vroom, 1964, Ladd & Lipset, 1973Ormsby & Watts, 1991;Hill, 1982;Hagedorn, 1994Hagedorn, , 1996Hagedorn, , 1998Hagedorn, & 2000Hagedorn & Sax, 1999;Rosser & Townsend, 2006) have sought to identify specific facets of faculty jobs that predict or influence satisfaction; often these researchers have come up with contradictory findings.…”
mentioning
confidence: 95%
“…Chi-square tests of significance were used to measure the association between the following variables: age, education, ethnicity, faculty perceptions, gender, marital status, teaching preparation methods, and work load diversity. The purpose for choosing these variables has to do with the need for further demographical studies (Benoit & Smith, 1980;M. D. Hill, 1983;Kallerberg, 1977) and the need to measure faculty work load activities in job satisfaction studies (Austin & Gamson, 1983;Wendel, 1977).…”
Section: Design and Instrumentationmentioning
confidence: 99%
“…The questionnaire used to measure faculty members' job satisfaction was constructed using other job satisfaction studies as guidelines for developing the survey (Benoit & Smith, 1980;Diener, 1985;Filan, Okun, & Witter, 1986;Friedlander, 1978;E. A. Hill, 1986;M.…”
Section: Design and Instrumentationmentioning
confidence: 99%
“…The two major areas of satisfaction were the same for both the 1978 and 1968 studies. The enjoyment of teaching and associating with and helping college-aged students were the first and second reasons given for satisfaction by the faculty members (cited in Benoit & Smith, 1980). Bess (1981) found that for most professionals, "intrinsic" satisfactions were the most valued factors in their motivation to work.…”
Section: Two-factor Theorymentioning
confidence: 99%